Thermal performance of backflow solar air heating with integrated nanoparticle enhanced pcm absorber storage system - Hayder, Ali Mohammed (2019)
The present study has been executed to clarify the advantage of using latent thermal storage integrated with a back pass solar air heater (SAH). The purpose of this study is to design, fabricate and evaluate the performance of SAH with integrated nanoparticles enhanced phase change material (PCM) absorber storage system. Three different SAH configurations have been designed and studied; without thermal storage, with thermal storage using paraffin wax as a PCM and with thermal storage using Al2O3-paraffin wax. A three-dimensional Navier-Stokes equation coupled with the energy balance equation is solved using the computational fluid dynamics (CFD) software program to implement numerical computations. The numerical analysis is conducted to determine the optimum collector dimensions in terms of length (L), width (W) and depth of air flow channel (Hch) at air mass flow rate of 0.03 kg/s and solar irradiance of 1000 W/m2. Results obtained from the numerical analysis indicate that the collector dimensions of (L = 1.8 m, W = 0.7 m, Hch = 0.07 m) which are the best design. The numerical results show that the SAH with Al2O3-paraffin wax have the thermal efficiency ranged between 73 % and 78 % with air temperature difference from 25 °C to 46.6 °C when the solar irradiance of 1000 W/m2 at the air mass flow rates of 0.03 kg/s and 0.06 kg/s, respectively. The experimental setup is constructed using these optimum dimensions for each configuration and validated using the numerical results. All configurations are fabricated and tested outdoor under the Iraq climatic conditions according to ASHRAE standard tests at different air mass flow rates. The two steps method is used to prepare the mixture of nanoparticles with PCM and ultrasonic device is used to suspend the nanoparticles in the PCM. The experimental results show that the SAH with Al2O3-paraffin wax has the highest daily performance and thermal efficiency followed by SAH with pure paraffin wax and SAH without storage. Moreover, the discharging time in the SAH with pure paraffin wax of heat stored took 5.5, 5, 4.5 and 4 hours at the air mass flow rate 0.03, 0.04, 0.05 and 0.06 kg/s, respectively. As for the SAH with Al2O3-paraffin wax, the discharge time are 5, 4.5, 4 and 3.5 hours at the air mass flow rates of 0.03, 0.04, 0.05 and 0.06 kg/s, respectively. The experimental results also show that increment in the thermal conductivity of PCM with the dispersion 1wt. % Al2O3 which led to raise the outlet air temperature and thermal efficiency of the SAH compared to SAH with pure paraffin wax. In addition, good agreement are obtained when comparing between the numerical and experimental results. It was the average differences in percentage on outlet air temperatures obtained in the numerical and experimental results from 2.11 % to 2.47 % and on the thermal efficiency from 2.70% to 3.50 %, respectively.